A bio-based polyester thermoplastic elastomer material and its preparation method and application
By optimizing the composition and processing technology of bio-based polyester thermoplastic elastomer materials, the contradictions in flame retardant performance, mechanical properties, melt flowability and surface properties are solved, and the coordinated adjustment and overall consideration of multiple properties are achieved to meet the high-performance needs of cable products.
Patent Information
- Application Number
- CN202510049394.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2045-01-13
AI Technical Summary
Bio-based polyester thermoplastic elastomer materials have contradictions in flame retardant properties, mechanical properties, melt fluidity and surface properties, and it is difficult to meet the multiple performance requirements of cable products at the same time.
By selecting suitable raw materials such as bio-based polyester thermoplastic elastomers, flame retardants, modifiers and dehydrated aluminum-magnesium hydrotalcite, systematic consideration and comprehensive experimental design, the composition and processing technology of the materials are optimized to achieve coordinated adjustment of flame retardant properties, mechanical properties, surface properties and melt flowability.
It realizes the UL94 V-2 grade flame retardant performance of bio-based polyester thermoplastic elastomer material, high tensile breaking strength and elongation, moderate Shore A hardness, good melt flowability and excellent surface performance, and meets the multiple performance requirements of cable products.
Smart Images

Figure CN119463425B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials, and in particular relates to a flame-retardant bio-based polyester thermoplastic elastomer material with high surface performance and capable of effectively adjusting mechanical properties and melt fluidity, and a preparation method and application thereof. Background Art
[0002] Polyester thermoplastic elastomer is a material with excellent comprehensive properties. Among various thermoplastic elastomer materials, it has the widest range of high and low temperature resistance, comprehensive and excellent mechanical properties, good oil and chemical resistance, and good processing performance. It is the preferred material for high-performance communication data cables, especially sheaths and components. The use of bio-based polyester polyether block copolymers derived from biomass raw materials as the base material to develop polyester thermoplastic elastomer materials can not only reduce carbon footprint and alleviate environmental pollution, but also save fossil resources, thereby providing a strong impetus for the sustainable application and development of this high-performance thermoplastic elastomer material, which is highly valued and expected by various application fields and market customers.
[0003] At present, there are very few reports on the successful commercialization of bio-based polyester thermoplastic elastomer flame retardant materials. In order to meet the performance and application requirements of leading domestic and foreign customers in the industry for this material, it is necessary to first use the VW-1 flame retardant grade specified in the cable product safety standard UL1581 as a benchmark. For the material flame retardant grade, it must at least reach UL94 V-2. It must also meet the corresponding cable product requirements for material hardness and other mechanical properties, melt fluidity, appearance and feel, scratch resistance, etc., so that the material has excellent and broad processing and product application performance. These are important technical difficulties that need to be solved for polyester thermoplastic elastomers, especially bio-based polyester thermoplastic elastomers, and are also urgent needs that continue to exist in the industry. For example, CN113039243 A discloses a thermoplastic elastomer compound, which comprises a hydrogenated styrene-farnesene-styrene block copolymer, a thermoplastic polyester elastomer with a bio-based content of at least about 45%, a polyolefin with a bio-based content of at least about 95%, a second styrene block copolymer, and a plasticizer, an antioxidant, etc., which is overmolded on a thermoplastic substrate with good adhesion. Although the thermoplastic elastomer compound has good adhesion, according to its performance test results, the hardness and mechanical properties cannot meet the requirements of cable products.
[0004] Therefore, polyester thermoplastic elastomer materials have many contradictions and even conflicts in achieving the above-mentioned properties, such as: 1) Due to the lack of compatibility between flame retardants and matrix resins, mechanical properties, surface properties or processing properties will suffer great losses while achieving flame retardant properties. For example, when the amount of flame retardant added is high, the flame retardant properties will be better, but the tensile strength of the material will be greatly reduced, the surface will be rough and not scratch-resistant, and there will be many precipitates that cannot be processed stably; 2) When flame retardant properties, mechanical properties and melt processing fluidity are all achieved, surface properties such as smoothness, scratch resistance and precipitation resistance are difficult to achieve good optimization or balance; 3) When surface modifiers and their combinations are used to improve the surface properties of materials, flame retardant properties, mechanical properties and melt fluidity will also be inevitably adversely affected. Summary of the invention
[0005] The present invention aims to facilitate the effective solution of the above problems through systematic consideration and comprehensive experimental design. These solutions are based on the simultaneous selection, adoption and application of various modification mechanisms of polymer materials (such as structural morphological characteristics and melt-mixing solubility of various materials, efficacy and synergy of various flame retardants, mechanical property regulation, melt fluidity regulation, comprehensive improvement of surface properties, etc.).
[0006] The object of the present invention is achieved through the following technical solution: providing a bio-based polyester thermoplastic elastomer material, comprising the following raw materials in parts by weight:
[0007] 50-80 parts of bio-based polyester thermoplastic elastomer;
[0008] Non-bio-based polyester thermoplastic elastomer 0-20 parts;
[0009] Polystyrene thermoplastic elastomer 0-10 parts;
[0010] Flame retardant 15-35 parts;
[0011] Modifier 1.5-7.5 parts;
[0012] Plasticizer 0-10 parts;
[0013] 0.3-1.5 parts of antioxidant;
[0014] 0.1-0.5 parts of dehydrated aluminum-magnesium hydrotalcite;
[0015] The bio-based polyester thermoplastic elastomer is a polyester polyether block copolymer with a biomass content greater than 50% and a moisture content of ≤0.05%;
[0016] The flame retardant comprises anhydrous zinc borate and a halogen-free flame retardant, wherein the halogen-free flame retardant is selected from at least two of diethyl aluminum hypophosphite, tert-butylphenyl diphenyl phosphate, resorcinol-bis(diphenyl phosphate), and melamine cyanurate;
[0017] The dehydrated aluminum-magnesium hydrotalcite has a water content of ≤0.03%.
[0018] In the present invention, the dehydrated aluminum-magnesium hydrotalcite (water content ≤ 0.03%) can not only improve the thermal stability of the material, but also significantly improve the flame retardant performance. Another important discovery is that it also has the function of adjusting the melt fluidity of the elastomer material. The dehydrated aluminum-magnesium hydrotalcite can be selected from Japan Kyowa Chemical DHT4a-2 and Zhenrui New Material HD9300. In the actual production process, the dehydrated aluminum-magnesium hydrotalcite can be dried in a vacuum oven at 210-250°C (preferably 230°C) for 2-3 hours to make the water content ≤ 0.03%.
[0019] Preferably, the bio-based polyester thermoplastic elastomer of the polyester polyether block copolymer with a biomass content greater than 50% can be selected from DSM Arnitel ECO400, SK Chemical Skypel ECO130D, Yijin 600-8250-009, Conai 0625-1, etc., preferably Yijin 600-8250-009. The biomass in these raw material grades is derived from industrial crop production areas and can be recycled. The source is reliable, the quality is stable, and it does not occupy agricultural land. In the actual production process, the polyester thermoplastic elastomer base material can be dried in a vacuum oven at 100-110°C for 3-5 hours to make the moisture content ≤0.05%. The main reason why the present invention adopts a high proportion of polyester polyether block copolymers with a biomass content greater than 50% is that it has high carbon reduction efficiency, but at the same time it brings higher difficulty in achieving various performance synergistically; while the use of polyester polyether block copolymers with a biomass content less than 50% has relatively weak carbon footprint reduction efficiency, the emission reduction and environmental benefits obtained are not obvious enough, and the performance synergistic adjustment based on this raw material is also relatively much easier.
[0020] When the Shore hardness or tensile strength of the elastomer material needs to be adjusted to a level significantly higher than that of the original bio-based thermoplastic polyester elastomer raw material, a non-bio-based polyester thermoplastic elastomer raw material is also added, which also helps to improve the UL94-V flame retardant performance. Preferably, the non-bio-based polyester thermoplastic elastomer is added in an amount of 5-20 parts, selected from non-bio-based polyester polyether block copolymers, such as DSM Arnitel EM400, Yijin TPEE 55D, and Kenai TPEE 55D.
[0021] In the present invention, diethyl aluminum hypophosphite can be selected from Exolit OP1230 of Clariant Chemicals of Switzerland, LFR08003 of Liside New Materials, and XS-FR-T315 of Xusen Flame Retardant; tert-butylphenyl diphenyl phosphate can be selected from Phosflex 71B HP of Akzo Nobel Chemicals of the Netherlands; resorcinol-bis(diphenyl phosphate) can be selected from WSFR-RDP of Wansheng Chemicals; melamine cyanurate can be selected from Melapur MC-25 of BASF of Germany, WD-MCA of Weidong Chemicals, and XS-MC-151 of Xusen Flame Retardant.
[0022] Preferably, the halogen-free flame retardant is selected from diethyl aluminum hypophosphite and melamine cyanurate, such as Xusen flame retardant XS-FR-T315 and Xusen flame retardant XS-MC-151.
[0023] Anhydrous zinc borate can be selected from Firebrake 500 of American borax, which is a flame retardant synergist in the scheme of the present invention. Preferably, the amount of the flame retardant synergist is 1-1.5 parts; more preferably 1.25 parts. When the flame retardant synergist is used, the synergistic effect of multiple halogen-free flame retardants on the flame retardant performance is one of the main tasks of the present invention.
[0024] Preferably, the modifier is selected from at least two of silicone masterbatch (such as Genioplast Pellet S from Wacker Chemicals, Germany), erucic acid amide (such as OXIOL E SPEZP from Emery Oil Chemicals, Croda ER-CH-MB (SI) from Croda Chemicals), high white nano-montmorillonite (such as sodium-based modified high white nano-montmorillonite from Haicheng Xingye Chemicals, Fenghong New Materials DK-4), ethylene-methyl methacrylate copolymer (EGMA) (such as Sumitomo Chemicals BF-E from Japan), and fumed silica (such as Evonik Specialty Chemicals A200 from Germany). More preferably, the modifier is selected from silicone masterbatch and erucic acid amide. The optimized combination of these modifiers can give the elastomeric material blending system significantly improved lubricity, dispersibility, compatibility, surface smoothness, scratch resistance, precipitation resistance, etc.; by selecting specific components and contents, excellent surface performance effects can be achieved. This part is also one of the main tasks of the present invention.
[0025] The styrene thermoplastic elastomer is a styrene-(ethylene-butylene)-styrene (SEBS) block copolymer. It is better to select SEBS with a soft block content of more than 35% for comprehensive adjustment of the Shore hardness, tensile strength and elongation of the elastomer material. Specifically, the styrene-(ethylene-butylene)-styrene (SEBS) block copolymer can be selected from American Kraton Polymer 1536HS, Japanese Asahi Chemical H1272, Sinopec Hunan Petrochemical YH-688, Boricon New Material R-506A, etc. Preferably, the styrene thermoplastic elastomer is 5-10 parts.
[0026] Preferably, the plasticizer is selected from one or more of epoxidized soybean oil (such as Eso Dehysol D81 from BASF, Germany), tert-butylphenyl diphenyl phosphate (flame retardant plasticizer), and resorcinol-bis(diphenyl phosphate) (flame retardant plasticizer). Epoxidized soybean oil mainly plays a plasticizing role, while the latter two can play a dual role of flame retardancy and plasticization.
[0027] Preferably, the antioxidant includes a hindered phenol antioxidant and a phosphite antioxidant. More preferably, the hindered phenol antioxidant is Irganox 1010 from BASF of Germany, and the phosphite antioxidant is Ultranox 626 from SI Group of the United States. The use of Irganox 1010 as a primary antioxidant and Ultranox 626 as a secondary antioxidant promotes better effects of anti-oxidation, anti-yellowing and anti-thermal oxidative aging.
[0028] The present invention also provides a method for preparing the above-mentioned bio-based polyester thermoplastic elastomer material, comprising the following steps: mixing and dispersing the raw materials uniformly, and then feeding them into a twin-screw extruder for extrusion and granulation to obtain an elastomer material. The details are as follows:
[0029] (1) Drying the polyester thermoplastic elastomer base material in a vacuum oven at 100-110°C for 3-5 hours to make the water content ≤0.05%; drying the dehydrated aluminum magnesium hydrotalcite in a vacuum oven at 210-250°C for 2-3 hours to make the water content ≤0.03%;
[0030] (2) Add the particles in the raw materials according to the formula ratio into a low-speed mixer and mix for 3-5 minutes until they are evenly dispersed;
[0031] (3) Add the powder material in the raw material into a high-speed mixer according to the formula ratio and mix at 400 RPM for 3-5 minutes until it is evenly dispersed;
[0032] (4) The uniformly mixed and dispersed granular material, powder material, and liquid material are fed into respective weight-loss metering feed scales, and fed into a twin-screw extruder by a starvation feeding method, and mixed, extruded, and granulated to obtain an elastomer material.
[0033] Preferably, the feeding section of the twin-screw extruder is set to a temperature of 185-195°C, the other sections are set to a temperature of 195-205°C, the screw speed is set to 150-250RPM, and the feeding rate is set to 15-25kg / h.
[0034] The bio-based polyester thermoplastic elastomer material of the present invention can be applied to communication data cable sheath products.
[0035] The present invention specifically optimizes and regulates flame retardant properties, mechanical properties, flow properties and surface properties on the basis of overall consideration by modifying bio-based polyester thermoplastic elastomers, and manufactures polyester thermoplastic elastomer materials that effectively meet specific application requirements, forming a series of varieties with a wider Shore hardness grade and melt flow grade, and its UL94 vertical combustion performance reaches V-2 grade, tensile breaking strength ≥8Mpa, tensile breaking elongation ≥500%, Shore A hardness 70-90, melt volume rate ≥10cm 3 / 10min, the material surface smoothness ≥ Level 3, scratch resistance ≥ Level 3, and precipitation resistance ≥ Level 3, which effectively expanded the application field of bio-based thermoplastic polyester elastomers and promptly solved the industry's very urgent technical problems under the new environmental protection situation.
[0036] Compared with the prior art, the present invention has the following beneficial features and effects:
[0037] The bio-based polyester thermoplastic elastomer material prepared by the combination of bio-based polyester thermoplastic elastomer, flame retardant, modifier type, content screening and dehydrated aluminum magnesium hydrotalcite can reach the flame retardant UL94 V-2 level, has high tensile strength at break (≥8Mpa) and elongation (≥500%), moderate Shore A hardness (70-90), good fluidity (melt volume rate ≥10cm 3 / 10min), with better material surface smoothness (≥level 3), scratch resistance (≥level 3) and precipitation resistance (≥level 3), achieving coordinated adjustment and consideration of flame retardant properties, mechanical properties, surface properties and processing properties.
[0038] Effective regulation of Shore hardness, tensile strength at break and elongation can be achieved through non-biobased polyester polyether block copolymers and / or styrene-(ethylene-butylene)-styrene (SEBS) block copolymers with various soft-hard block ratios and / or liquid plasticizer epoxidized soybean oil or liquid flame-retardant plasticizer tert-butylphenyl diphenyl phosphate or resorcinol-bis(diphenyl phosphate), while flame retardant performance requirements can be guaranteed.
[0039] Under the condition that the Shore hardness, tensile strength at break and elongation remain basically unchanged, a unique and effective method is realized by utilizing the strong hydrolysis characteristics of polyester raw materials to reasonably control the melt volume rate (≥10cm 3 / 10min) to meet the requirements of various cable extrusion coating processes and component injection molding processes.
[0040] Through the modifier, good lubrication, dispersion, melt mixing and / or appropriate system compatibility stability are formed between various thermoplastic elastomer components with different structural forms or large solubility differences in the material, such as polyesters and styrenes, and between the above high molecular weight material components and low molecular weight material components, such as various phosphorus or nitrogen flame retardants or antioxidants, dehydrated aluminum magnesium hydrotalcite, etc., which not only effectively reduces the separation and precipitation of small molecular materials, but also promotes a phase morphology structure with high melt mixing homogeneity between high molecular weight materials, and also realizes the required combination of internal and external lubrication effects, thereby obtaining superior properties such as a smooth and high-quality material surface and good scratch resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings in the following description are some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying any creative work.
[0042] Figure 1 The appearance of the 0.8 mm burning specimens of Example 4, Example 1, and Comparative Example 4 (from left to right) after the UL94 V burning test;
[0043] Figure 2 The appearance of the 1.6 mm burning specimens of Example 4, Example 1, and Comparative Example 4 (from left to right) after the UL94 V burning test;
[0044] Figure 3 This is the extruded material strip sample of the surface feel smoothness test of Comparative Example 9;
[0045] Figure 4 This is the extruded material strip sample of the surface feel smoothness test in Example 8;
[0046] Figure 5 This is the extruded material strip sample of the surface feel smoothness test in Example 4;
[0047] Figure 6 This is the extruded material strip sample after the surface scratch resistance test of Comparative Example 9;
[0048] Figure 7 This is the extruded material strip sample after the surface scratch resistance test of Example 1;
[0049] Figure 8 This is the extruded material strip sample after the surface scratch resistance test of Example 5;
[0050] Fig. 9 This is the extruded material strip sample of the extrusion die head precipitation resistance test of comparative example 9;
[0051] Fig.10 The extruded material strip sample of the extrusion die head precipitation resistance test in Example 1;
[0052] Fig.11 This is the extruded material strip sample for the extrusion die head precipitation resistance test in Example 5. DETAILED DESCRIPTION
[0053] The technical scheme of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0054] The raw materials used in the following examples and comparative examples of the present invention can all be purchased from the market. The types, components, brands and manufacturer information of the raw materials are shown in Table 1.
[0055] Table 1 Types, ingredients, brands and manufacturers of raw materials used in examples / comparative examples
[0056]
[0057] Table 1
[0058]
[0059] The various properties and characterization methods of the materials in the present invention are as follows:
[0060] (1) Density: tested according to ISO1189 standard;
[0061] (2) Melt flow rate: tested according to ISO1133 standard (230°C, 2.16kg);
[0062] (3) Shore A hardness: tested according to ISO868 standard;
[0063] (4) Tensile mechanical properties: tested according to ISO3167 standard;
[0064] (5) Flame retardant performance: tested according to UL94V standard;
[0065] (6) Extruded strip surface smoothness: The extruded strip surface smoothness test evaluation method is as follows.
[0066] 6.1 Test evaluation conditions
[0067] The test evaluation shall be carried out on the day when the test material is extruded, with the temperature and humidity conditions being 23±5°C and 50±20%RH, and the test observation and evaluation shall be carried out at close range under fluorescent light with good illumination.
[0068] 6.2 Test evaluation method
[0069] Sample preparation: First, the twin-screw compounding extruder unit is allowed to reach a stable state during the extrusion of the test material. Then, a sample of about 80 cm long extruded material strips is directly cut after extrusion cooling and before pelletizing. During the stable period of the test, a total of 6 representative extruded material strip samples are cut for averaging the test evaluation results.
[0070] Test: Two test methods, visual observation and touch feeling, are used to confirm the hand feel smoothness. Visual observation mainly checks the surface roughness and orange peel appearance of the extruded material strip sample from a visual perspective, and touch mainly confirms the surface granularity and smoothness. The hand feel smoothness index is divided into five levels from low to high, 1, 2, 3, 4, and 5. The basis for judging each level is shown in Table 2 below:
[0071] Table 2 Criteria for judging the level of hand smoothness
[0072]
[0073] (7) Scratch resistance of extruded strip surface: The scratch resistance of extruded strip surface was evaluated according to the following test method.
[0074] 7.1 Test evaluation conditions
[0075] The test evaluation shall be carried out on the day when the test material is extruded, with the temperature and humidity conditions being 23±5°C and 50±20%RH, and the test observation and evaluation shall be carried out at close range under fluorescent light with good illumination.
[0076] 7.2 Test evaluation method
[0077] Sample preparation: First, the twin-screw compounding extruder unit is allowed to reach a stable state during the extrusion of the test material. Then, a sample of about 80 cm long of the extruded material strip after extrusion cooling and before pelletizing is directly cut. A total of 6 representative extruded material strip samples are cut during the test stabilization period to average the test evaluation results.
[0078] Test: Use a fingernail perpendicular to the length direction of the extruded material strip sample, apply 1.0N pressure to the surface of the extruded material strip sample and scrape it along the length direction of the extruded material strip sample for about 5-10cm, then observe and measure the white marks on the surface of the extruded material strip sample, the deformation and warping of the scraping moving section, and the particle shedding. The surface scratch resistance index is divided into five levels from low to high: 1, 2, 3, 4, and 5. The basis for judging each level is shown in Table 3 below:
[0079] Table 3 Criteria for determining scratch resistance level
[0080]
[0081] (8) Extrusion die precipitation resistance: The following extrusion die precipitation resistance test evaluation method is used.
[0082] 8.1 Test evaluation conditions
[0083] Carry out under extrusion site conditions and ensure good lighting.
[0084] 8.2 Test evaluation method
[0085] Sample preparation: First, make the twin-screw compounding extruder unit reach a stable state during the extrusion of the test material, immediately scrape off the extrudate and die precipitates, and clean the entire surface of the die extrusion port; then start drawing the strip. After 5 minutes, a relatively regular ring-shaped precipitate will form around the extrusion strip sample at the die extrusion port.
[0086] Test: Observe and measure the maximum width and thickness of the ring-shaped precipitate, take photos and record its shape. The extrusion die head precipitation resistance index is divided into five levels from low to high: 1, 2, 3, 4, 5. The basis for judging each level is shown in Table 4 below:
[0087] Table 4 Criteria for judging the level of die head precipitation resistance
[0088]
[0089] According to the comprehensive performance requirements of the application, the present invention stipulates the main performance indicators of the material as follows: UL94 vertical combustion performance reaches V-2 level, tensile strength at break ≥ 8Mpa and elongation ≥ 500%, Shore A hardness 70-90, melt volume rate ≥ 10cm 3 / 10min, the material surface smoothness ≥ Grade 3, the scratch resistance ≥ Grade 3 and the precipitation resistance ≥ Grade 3. Such performance indicators can clearly reflect the performance level that the material of the present invention needs to achieve and confirm the balanced adjustment of various performance levels, thereby fully realizing the material application requirements.
[0090] The preparation methods of the polyester thermoplastic elastomer materials of the following examples and comparative examples are as follows:
[0091] (1) Dry the polyester thermoplastic elastomer base material in a vacuum oven at 105°C for 4 hours to make the water content ≤0.05%; dry the dehydrated aluminum magnesium hydrotalcite in a vacuum oven at 230°C for 3 hours to make the water content ≤0.03%;
[0092] (2) Add the particle raw materials in the raw materials according to the formula ratio into a low-speed mixer and mix for 4 minutes until they are evenly dispersed;
[0093] (3) Add the powdered raw materials in the raw materials into a high-speed mixer according to the formula ratio and mix at 400 RPM for 4 minutes until they are evenly dispersed;
[0094] (4) The uniformly mixed and dispersed particle raw materials, powder raw materials, and liquid raw materials (if any) are fed into respective weight-loss metering feed scales, and fed into a twin-screw extruder by a starvation feeding method, and mixed, extruded, and granulated to obtain an elastomer material.
[0095] 1) Debugging test mainly focusing on mechanical properties
[0096] The raw material components of the bio-based polyester thermoplastic elastomer materials of Examples 1-13 are shown in Table 5:
[0097] Table 5 Raw material components of bio-based polyester thermoplastic elastomer materials of Examples 1-13
[0098]
[0099] In the process of exploring the mechanical properties of polyester thermoplastic elastomer materials, the present invention prepared polyester thermoplastic elastomer materials of comparative examples 1-10 with reference to Example 1. The raw material components of the polyester thermoplastic elastomer materials of comparative examples 1-10 are shown in Table 6:
[0100] Table 6 Raw material components of polyester thermoplastic elastomer materials of comparative examples 1-10
[0101]
[0102] The performance results of the bio-based polyester thermoplastic elastomer materials of Examples 1-13 are shown in Table 7:
[0103] Table 7 Performance results of bio-based polyester thermoplastic elastomer materials of Examples 1-13
[0104]
[0105] Note: The UL94 flame retardant test result is the total burning time, which is the sum of the time it takes for 5 burning samples to continue burning for 10 seconds after being ignited twice and then self-extinguished, the same below.
[0106] The performance results of the polyester thermoplastic elastomer materials of Comparative Examples 1-10 are shown in Table 8:
[0107] Table 8 Performance results of polyester thermoplastic elastomer materials of Comparative Examples 1-10
[0108]
[0109] The appearance of the 0.8 mm burning specimens of Example 1, Example 4 and Comparative Example 4 after the combustion test is as follows: Figure 1As shown, from left to right are Example 4, Example 1, and Comparative Example 4: the combustion sample of Example 4 slightly foamed after combustion, and the combustion sample of Example 1 was slightly carbonized after combustion; the combustion sample of Comparative Example 4 was completely burned and heavily carbonized; the appearance of the 1.6 mm combustion samples of Example 1, Example 4, and Comparative Example 4 after the combustion test is as follows Figure 2 As shown, from left to right are Example 4, Example 1, and Comparative Example 4: the combustion sample of Example 4 is moderately foamed after combustion, and the combustion sample of Example 1 is slightly carbonized after combustion; the combustion sample of Comparative Example 4 is heavily carbonized.
[0110] Comparative Example 9: The extruded material strip sample of the surface feel smoothness test is as follows Figure 3 As shown; Example 8 surface feel smoothness test extruded material strip sample as shown Figure 4 As shown; Example 4 Surface feel smoothness test extruded material strip sample as shown Figure 5 shown.
[0111] Comparative Example 9: The extruded material strip sample after the surface scratch resistance test is as follows Figure 6 As shown; Example 1 after the surface scratch resistance test of the extruded material strip sample as shown Figure 7 As shown; Example 5 surface scratch resistance test after the extruded material strip sample as shown Figure 8 shown.
[0112] Comparative Example 9: The extruded material strip sample of the extrusion die head precipitation resistance test is as follows Fig. 9 As shown; Example 1 Extrusion die head precipitation resistance test extrusion strip sample as shown Fig.10 As shown; Example 5 extrusion die head precipitation resistance test extrusion strip sample as shown Fig.11 shown.
[0113] It can be seen from the test results of Table 7 and Table 8 that the materials prepared in Examples 1-13 of the present invention have UL94 vertical flammability that can reach V-2 level, have high tensile strength at break (≥8Mpa) and elongation (≥500%), moderate Shore A hardness (70-90), and good fluidity (melt volume rate ≥10cm 3 / 10min), with better material surface smoothness (≥level 3), scratch resistance (≥level 3) and precipitation resistance (≥level 3), achieving coordinated adjustment and overall consideration of flame retardant properties, mechanical properties, surface properties and processing properties.
[0114] The polyester thermoplastic elastomer materials of Comparative Examples 1-10 cannot achieve coordinated adjustment and overall consideration of flame retardancy, mechanical properties, surface properties and processing properties.
[0115] 2) Debugging test mainly focusing on surface performance
[0116] The raw material components of the bio-based polyester thermoplastic elastomer materials of Examples 14-19 are shown in Table 9:
[0117] Table 9 Raw material components of bio-based polyester thermoplastic elastomer materials of Examples 14-19
[0118]
[0119] In the process of exploring the surface performance adjustment of polyester thermoplastic elastomer materials, the present invention prepared polyester thermoplastic elastomer materials of comparative examples 11-21 with reference to Example 1. The raw material components of the polyester thermoplastic elastomer materials of comparative examples 11-21 are shown in Table 10:
[0120] Table 10 Raw material components of polyester thermoplastic elastomer materials of comparative examples 11-21
[0121]
[0122] The performance results of the bio-based polyester thermoplastic elastomer materials of Examples 14-19 are shown in Table 11:
[0123] Table 11 Performance results of bio-based polyester thermoplastic elastomer materials of Examples 14-19
[0124]
[0125] The performance results of the polyester thermoplastic elastomer materials of Comparative Examples 11-21 are shown in Table 12:
[0126] Table 12 Performance results of polyester thermoplastic elastomer materials of Comparative Examples 11-21
[0127]
[0128] It can be seen from the test results of Table 11 and Table 12 that the materials prepared in Examples 14 to 19 of the present invention have a UL94 vertical flammability of V-2, have a relatively high tensile strength at break (≥8Mpa) and elongation (≥500%), a moderate Shore A hardness (70-90), and good fluidity (melt volume rate ≥10cm 3 / 10min), with better material surface smoothness (≥level 3), scratch resistance (≥level 3) and precipitation resistance (≥level 3), achieving coordinated adjustment and overall consideration of flame retardant properties, mechanical properties, surface properties and processing properties.
[0129] The polyester thermoplastic elastomer materials of Comparative Examples 11-21 cannot achieve coordinated adjustment and overall consideration of flame retardancy, mechanical properties, surface properties and processing properties.
[0130] 3) Debugging test mainly focusing on flow performance
[0131] The raw material components of the bio-based polyester thermoplastic elastomer materials of Examples 20-28 are shown in Table 13:
[0132] Table 13 Raw material components of bio-based polyester thermoplastic elastomer materials of Examples 20-28
[0133]
[0134] In the process of exploring the flow performance adjustment of polyester thermoplastic elastomer materials, the present invention prepared polyester thermoplastic elastomer materials of comparative examples 22-27 with reference to Example 1. The raw material components of the polyester thermoplastic elastomer materials of comparative examples 22-27 are shown in Table 14:
[0135] Table 14 Raw material components of polyester thermoplastic elastomer materials of comparative examples 22-27
[0136]
[0137] The performance results of the bio-based polyester thermoplastic elastomer materials of Examples 20-28 are shown in Table 15:
[0138] Table 15 Performance results of bio-based polyester thermoplastic elastomer materials of Examples 20-28
[0139]
[0140] The performance results of the polyester thermoplastic elastomer materials of Comparative Examples 22-27 are shown in Table 16:
[0141] Table 16 Performance results of polyester thermoplastic elastomer materials of Comparative Examples 22-27
[0142]
[0143] It can be seen from the test results of Table 15 and Table 16 that the materials prepared in Examples 20-28 of the present invention have UL94 vertical flammability that can reach V-2 level, have high tensile strength at break (≥8Mpa) and elongation (≥500%), moderate Shore A hardness (70-90), and good fluidity (melt volume rate ≥10cm 3 / 10min), with better material surface smoothness (≥level 3), scratch resistance (≥level 3) and precipitation resistance (≥level 3), achieving coordinated adjustment and overall consideration of flame retardant properties, mechanical properties, surface properties and processing properties.
[0144] The polyester thermoplastic elastomer materials of Comparative Examples 22-27 cannot achieve coordinated adjustment and overall consideration of flame retardancy, mechanical properties, surface properties and processing properties.
[0145] 4) Debugging test mainly focusing on flame retardancy
[0146] The raw material components of the bio-based polyester thermoplastic elastomer materials of Examples 29-39 are shown in Table 17:
[0147] Table 17 Raw material components of bio-based polyester thermoplastic elastomer materials of Examples 29-39
[0148]
[0149] In the process of exploring the flame retardant performance of polyester thermoplastic elastomer materials, the present invention prepared polyester thermoplastic elastomer materials of comparative examples 28-40 with reference to Example 1. The raw material components of the polyester thermoplastic elastomer materials of comparative examples 28-40 are shown in Table 18:
[0150] Table 18 Raw material components of polyester thermoplastic elastomer materials of comparative examples 28-40
[0151]
[0152] The performance results of the bio-based polyester thermoplastic elastomer materials of Examples 29-39 are shown in Table 19:
[0153] Table 19 Performance results of bio-based polyester thermoplastic elastomer materials of Examples 29-39
[0154]
[0155] The performance results of the polyester thermoplastic elastomer materials of Comparative Examples 28-40 are shown in Table 20:
[0156] Table 20 Performance results of polyester thermoplastic elastomer materials of comparative examples 28-40
[0157]
[0158] It can be seen from the test results of Table 19 and Table 20 that the materials prepared in Examples 29-39 of the present invention have a UL94 vertical flammability of V-2, have a high tensile strength at break (≥8Mpa) and elongation (≥500%), a moderate Shore A hardness (70-90), and good fluidity (melt volume rate ≥10cm 3 / 10min), with better material surface smoothness (≥level 3), scratch resistance (≥level 3) and precipitation resistance (≥level 3), achieving coordinated adjustment and overall consideration of flame retardant properties, mechanical properties, surface properties and processing properties.
[0159] The polyester thermoplastic elastomer materials of Comparative Examples 28-40 cannot achieve coordinated adjustment and overall consideration of flame retardancy, mechanical properties, surface properties and processing properties.
[0160] Other tests
[0161] Comparative Example 41
[0162] The difference between this comparative example and Example 1 is that: the bio-based polyester polyether block copolymer 600-8250-009 is not dried and has a moisture content of 0.57%; the other components are the same as those in Example 1;
[0163] Comparative Example 42
[0164] The difference between this comparative example and Example 1 is that: undried dehydrated aluminum-magnesium hydrotalcite is used, and the water content is 0.26%; the other components are the same as those in Example 1.
[0165] The performance results of the polyester thermoplastic elastomer materials of Comparative Example 41 and Comparative Example 42 are shown in Table 21:
[0166] Table 21 Performance results of polyester thermoplastic elastomer materials of Comparative Examples 41 and 42
[0167]
[0168] It can be seen from the test results in Table 21 that the polyester thermoplastic elastomer materials of Comparative Examples 41-42 cannot achieve coordinated adjustment and overall consideration of flame retardancy, mechanical properties, surface properties and processing properties.
[0169] It can be seen from the performance test results of the above embodiments and comparative examples that the bio-based polyester thermoplastic elastomer materials of the embodiments of the present invention effectively achieve the coordinated adjustment and overall consideration of the flame retardant, mechanical, surface and processing properties required for the bio-based polyester thermoplastic elastomer materials in high-end cable product related applications through the selection and combination of multiple raw materials, and also open up effective industrial applications based on a large proportion of bio-based polyester elastomer low-carbon footprint raw materials; the realization of the performance required for these important applications is based on the in-depth exploration and utilization of the mechanisms and functions of numerous raw materials and additives and the confirmation of synergy, which has been confirmed through a large number of corresponding related combination tests including cable product processing application tests, and therefore has reliable practicality.
[0170] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can easily think of various equivalent modifications or replacements within the technical scope disclosed by the present invention, and these modifications or replacements should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be based on the protection scope of the claims.
Claims
1. A bio-based polyester thermoplastic elastomer material, characterized in that: Each 100 parts by weight contains the following raw materials: 50-80 parts of bio-based polyester thermoplastic elastomer; Non-bio-based polyester thermoplastic elastomer 0-20 parts; Polystyrene thermoplastic elastomer 0-10 parts; Flame retardant 15-35 parts; Modifier 1.5-7.5 parts; Plasticizer 0-10 parts; 0.3-1.5 parts of antioxidant; 0.1-0.5 parts of dehydrated aluminum-magnesium hydrotalcite; The bio-based polyester thermoplastic elastomer is a polyester polyether block copolymer with a biomass content greater than 50% and a moisture content of ≤0.05%; The flame retardant comprises anhydrous zinc borate and a halogen-free flame retardant, wherein the halogen-free flame retardant is selected from at least two of diethyl aluminum phosphinate, tert-butylphenyl diphenyl phosphate, resorcinol-bis(diphenyl phosphate), and melamine cyanurate; The modifier is selected from at least two of silicone masterbatch, erucamide, high white nano-montmorillonite, ethylene-methacrylate glycidyl copolymer, and fumed silica, and must contain silicone masterbatch and erucamide; The dehydrated aluminum-magnesium hydrotalcite has a water content of ≤0.03%.
2. The bio-based polyester thermoplastic elastomer material according to claim 1, characterized in that: The polystyrene thermoplastic elastomer is a styrene-(ethylene-butylene)-styrene block copolymer.
3. The bio-based polyester thermoplastic elastomer material according to claim 2, characterized in that: The soft block content of the styrene-(ethylene-butylene)-styrene block copolymer is more than 35%.
4. The bio-based polyester thermoplastic elastomer material according to claim 1, characterized in that: The plasticizer is selected from one or more of epoxy soybean oil, tert-butylphenyl diphenyl phosphate, and resorcinol-bis(diphenyl phosphate).
5. The bio-based polyester thermoplastic elastomer material according to claim 1, characterized in that: The antioxidants include hindered phenol antioxidants and phosphite antioxidants.
6. The bio-based polyester thermoplastic elastomer material according to claim 5, wherein the hindered phenol antioxidant is Irganox 1010, and the phosphite antioxidant is Ultranox 626.
7. The bio-based polyester thermoplastic elastomer material according to claim 1, characterized in that: The water content of the non-biobased polyester thermoplastic elastomer is ≤0.05%.
8. The bio-based polyester thermoplastic elastomer material according to claim 1, characterized in that: The halogen-free flame retardant is selected from aluminum diethylphosphinate and melamine cyanurate; and the modifier is selected from silicone masterbatch and erucamide.
9. A method for preparing a bio-based polyester thermoplastic elastomer material according to any one of claims 1 to 8, characterized in that: The method comprises the following steps: mixing and dispersing the raw materials into particle materials, powder materials and liquid materials respectively and then feeding the raw materials into a twin-screw mixing extruder through corresponding metering feeders for extrusion and granulation to obtain an elastomer material.
10. Use of the bio-based polyester thermoplastic elastomer material according to any one of claims 1 to 8 in high-performance communication data cable sheaths.
Citation Information
Patent Citations
Overmolding thermoplastic elastomer compounds having high bio-based content
CN113039243A
Thermoplastic polyester elastomer composition and preparation method thereof
CN102477212A
Halogen-free flame-retardant elastomer composition
CN102775740A